Tinjauan Yuridis Pemungutan Liar di Jembatan Barelang Kota Batam berdasarkan Peraturan Daerah Kota Batam Nomor 3 Tahun 2018 Tentang Penyelenggaraan dan Retribusi Parkir - Tantimin Tantimin; Elvi Elvi (Fakultas Hukum, Universitas Internasional Batam, 2019)
This Final Project Research aims to analyze and find out the collection of parking at the Batam City Barelang Bridge including illegal collection and to describe the role of the Batam City Transportation Agency in implementing or enforcing Batam City Regulation Number 3 of 2018 concerning Parking Management and Retribution. The research methodology used by the author is empirical legal research by examining the results of observations and interviews and is supported by legal theories and legislation in force in Indonesia. The type of data used is primary data as primary data and secondary data as supporting data consisting of primary, secondary and tertiary legal materials. This Legal Research is analyzed descriptively qualitatively. The results of the study that the authors obtained from observations and interviews were then reviewed from the theory of Economic Development according to Anwar that the tariffs for parking at the Batam City Barelang Bridge provided were not in accordance with Batam City Regulation Number 3 of 2018 concerning the Implementation and Retribution of Parking and Previously the City Transportation Agency Batam insists there are no rules that specify parking fees for tourist areas and the Batam City Transportation Agency as the related agency appointed by the Batam City Government to play an important role in Implementing or Enforcing Batam City Regulation Number 3 of 2018 concerning Implementation and Retribution of Parking Limitation as the Regulator, Facilitator, and Dynamicsator